ESTONIAN "EDUCATIONAL MIRACLE" WHICH UKRAINE CAN USE - Sitkar, Viktor Illich; Sitkar, Stepan Viktorovych (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
Education is considered to be a key factor in the sustainable development of a state throughout the world. A good example in this regard is the Estonian experience. This country is in the leader in PISA 2018 educational systems rating. The Estonian “educational wonder” lies in the following factors: 1) anyone, regardless of the individual characteristics, has a right to obtain good education; 2) the emphasis is made on the fact, that school starts with a teacher. Thus, teachers are given much more freedom to form a curriculum because there is no rigorous formalized study plan. There only expectation from a teacher is the result, yet there are no restrictions on how to achieve it. 3) Estonian students are educated to be more independent. 4) School prepares children for life, and not only for final exams. Lots of attention is paid to the formation of social skills. 5) Children are taught to respect themselves and others, which is one of the major values of European society.